مساهمة في دراسة التنوع الحيوي لصغار أسماك المياه العذبة في بعض الأوساط المائية للساحل السوري - غالية محمد; فاضل إقبال (Latakia University Journal -Basic Sciences Series, 2018)
أظهرت الدراسة الحقلية والمخبرية خلال عامي (1999-2000م)، للمجموع الحيواني والفونا السمكية المرافقة (صغار الأسماك) في عدد من الأوساط المائية العذبة (نهر الكبير الجنوبي، نهر الأبرش، نهر الحصين، نهر القش، سدّ 16 تشرين، سدّ بللوران، سدّ الحفة)، وجود صغار تسعة أنواع سمكية تنتمي إلى سبع فصائل: ثلاثة أنواع منها إلى الفصيلة الكاربية Cyprinidae، ونوع واحد لكل من الفصائل Cichlidae، Blenniidae، Cobitidae، Gasterosteidae، Mugilidae، Poeciliidae. منها مايسجّل وجوده لأول مرة خلال الأربعة عقود الأخيرة، وهو Blennius fluviatilis. كما بلغ عددها الإجمالي /615/ فرداً، كان أغزرها مصادفة هو السمكة آكلة البعوض (الغمبوزيا) Gambusia affinis holbrooki الذي وجد وسجّل في جميع المحطات المدروسة، وعلى مدار العام تقريباً. وقد تبيّن أنه خلال فترة البحث، كان سدّ 16 تشرين هو المحطة الأكثر تنوعاً من حيث تعداد الأنواع السمكية. The field and laboratory study was conducted in (1999- 2000) on fauna and Ichthiofauna follower (young fish) in some fresh water environment (Big Southern river, Abrash river, Al-Houssin river, Al-Kosh river, 16th of October dam, Ballouran dam and Al-Haffa dam) showed the presence of nine species of young fish belonging to seven families: three species of them follow the carp family Cyprinidae, and one species for each of the following families: Blenniidae, Cichlidae, Cobitidae, Gasterosteidae, Mugilidae and Poeciliidae. The presence of some of these was recorded for the first time in the last for decades (Blennius fluviatilis). The total number reached to (615) individuals. The most frequent one was the mosqueto fish (Gambusia affinis holbrooki) which were found and recorded in all the studied stations, during the year. It was found, during the period of this study, that the 16th October dam was the station that has the most diversity in number of fish species.